A machine learning framework to measure Water Drop Penetration Time (WDPT) for soil water repellency analysis - Danxu Wang; Emma Regentova; Venkatesan Muthukumar; Markus Berli; Frederick C. Harris, Jr. (Machine Learning with Applications)
The heat from wildfires volatilizes soil’s organic compounds which form a waxy layer when condensed on cooler soil particles causing soil to repel water. Timely assessment of soil water repellency (SWR) is critical for prediction and prevention of detrimental impacts of hydrophobic soils such as soil erosion, reduced availability of water to plants, and water runoff after rainfalls leading to floods. The Water Drop Penetration Time (WDPT), i.e., the time elapsed from a drop landing on the soil surface to its complete absorption is commonly used to assess the SWR level. Its manual measurements have variability based on the used instruments and subjective observations. The goal of this work is to design an automated system to perform standardized WDPT tests and assess the SWR levels. It consists of an electronically controlled mechanism to release a water drop, and a video camera to record the water penetration process. The latter is modeled as an “action” in video and Temporal Action Localization (TAL) analytics is used for predicting the WDPT and assessing the SWR level.